Characterization of volatile organic compounds with anti-atherosclerosis effects in Allium macrostemon Bge. and Allium chinense G. Don by head space solid phase microextraction coupled with gas chromatography tandem mass spectrometry - Qin, Zifei; Duan, Shuyi; Li, Yuan; Li, Xinqiang; Xing, Han; Yao, Zhihong; Zhang, Xiaojian; Yao, Xinsheng; Yang, Jing (Frontiers in Nutrition, 2023)
Allium macrostemon Bge. (AMB) and Allium chinense G. Don (ACGD) are both edible Allium vegetables and named officinal Xiebai (or Allii Macrostemonis Bulbus) in East Asia. Their medicinal qualities involve in lipid lowering and anti-atherosclerosis effects. And steroidal saponins, nitrogenous compounds and sulfur compounds are like the beneficial components responsible for medicinal functions. Sulfur compounds are the recognized main components both in the volatile oils of AMB and ACGD. Besides, few researches were reported about their holistic chemical profiles of volatile organic compounds (VOCs) and pharmacodynamic effects. In this study, we first investigated the lipid-lowering and anti-atherosclerotic effects of volatile oils derived from AMB and ACGD in ApoE-/- mice with high fat and high cholesterol diets. The results showed the volatile oils of AMB and ACGD both could markedly reduce serum levels of TG, TC and LDL-C (p < 0.05), and had no alterations of HDL-C, ALT and AST levels (p > 0.05). Pathological results displayed they both could obviously improve the morphology of cardiomyocytes and the degree of myocardial fibrosis in model mice. Meanwhile, oil red O staining results also proved they could apparently decrease the lesion areas of plaques in the aortic intima (p < 0.05). Furthermore, head space solid phase microextraction coupled with gas chromatography tandem mass spectrometry combined with metabolomics analysis was performed to characterize the VOCs profiles of AMB and ACGD, and screen their differential VOCs. A total of 121 and 115 VOCs were identified or tentatively characterized in the volatile oils of AMB and ACGD, respectively. Relative-quantification results also confirmed sulfur compounds, aldehydes, and heterocyclic compounds accounted for about 85.6% in AMB bulbs, while approximately 86.6% in ACGD bulbs were attributed to sulfur compounds, ketones, and heterocyclic compounds. Multivariate statistical analysis showed 62 differentially expressed VOCs were observed between AMB and ACGD, of which 17 sulfur compounds were found to be closely associated with the garlic flavor and efficacy. Taken together, this study was the first analysis of holistic chemical profiles and anti-atherosclerosis effects of AMB and ACGD volatile oils, and would benefit the understanding of effective components in AMB and ACGD.